(untitled) (Bangladesh Journal of Medical Science, 2017)
Geographical distance from health centre and the costs and constraints involved in cold chain maintenance are important factors influencing poor immunization coverage in remote areas of resource-limited countries. Controlled temperature chain (CTC) is an approach which uses the innate heat stability specific to certain vaccines, to reduce the dependency on cold chain and has been accepted for potential use in situations where cold chain maintenance is not feasible and limits immunization programme effectiveness. In 2012, MenAfriVac, Meningitis A conjugate vaccine became the first vaccine to be pre-qualified by World Health Organization for use under CTC. Various existing vaccines are being approved for CTC use in low-resource settings. Proper CTC labelling and effective temperature monitoring are important considerations. While cold chain is critical and should be maintained as always, CTC is a useful alternate option which needs to be explored to reach the unreached in limited-resource settings. Bangladesh Journal of Medical Science Vol.16(3) 2017 p.477-479